Gender differences in health in later life: The new paradox? - Arber, Sara; Cooper, Helen (Social Science & Medicine, 1999)
This paper examines gender differences in health, based on data from over 14,000 men and women aged 60 and above from 3 years of the British General Household Survey, 1992±1994. There is little difference between the sexes in the reporting of self-assessed health and limiting longstanding illness, but older women are substantially more likely to experience functional impairment in mobility and personal self-care than men of the same age. These ®ndings persist after controlling for the dierential social position of men and women according to their marital status, social class, income and housing tenure. The results reveal a paradox in health reporting among older people; for a given level of disability, women are less likely to assess their health as being poor than men of the same age after accounting for structural factors. Older women's much higher level of functional impairment co-exists with a lack of gender difference in self-assessed health. # 1998 Elsevier Science Ltd. All rights reserved
Keywords: 1900-1999; 1990-1999; discipline; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sociologie; thématiques; vieillesse